Interferon‐γ release assay for tuberculosis in patients with psoriasis treated with tumour necrosis factor antagonists: in vivo and in vitro analysis. (31st October 2013) - Sauzullo, I.; Mengoni, F.; Marocco, R.; Potenza, C.; Skroza, N.; Tieghi, T.; Lichtner, M.; Vullo, V.; Mastroianni, C.M.
Summary: Background: Screening for latent tuberculosis infection (LTBI) is mandatory in patients with psoriasis prior to starting on tumour necrosis factor (TNF) blockers. Objectives: To investigate the longitudinal changes of interferon (IFN)‐γ response to Mycobacterium tuberculosis ‐specific antigens by serial QuantiFERON‐TB Gold In‐Tube (QFT‐GIT) testing in patients with psoriasis during long‐term anti‐TNF therapy. The direct in vitro effect of adalimumab on IFN‐γ secretion was also evaluated. Methods: In total, 148 patients with psoriasis designated to start anti‐TNF treatment were enrolled. We performed a tuberculin skin test at screening, and QFT‐GIT at baseline and serially for 24 months after TNF antagonist onset. Results: At screening, QFT‐GIT was positive in 22·3% of the patients, negative in 73·6% and indeterminate in 4%. The IFN‐γ response following isoniazid therapy declined and became QFT‐GIT negative in 8% of 26 patients with LTBI; in 69% of subjects with LTBI the QFT‐GIT remained persistently positive with a significant increase of IFN‐γ levels during the follow‐up, even if no cases of active tuberculosis were found. Variations of IFN‐γ levels were observed also in 7% of 27 patients without LTBI who switched to positive QFT‐GIT after 12 or 18 months of biologic therapy, suggesting a new occurrence or reactivation of LTBI. In vitro data showed that in the presence of adalimumab the IFN‐γ levels were significantly reduced in a dose‐dependent manner ( P  <   0·05). Conclusions: Fluctuations of IFN‐γ release may occur in patients with psoriasis treated with TNF antagonists. The clinical use of repeated blood tests and the correct interpretation of individual IFN‐γ changes could be useful in identifying possible cases of LTBI reactivation or newly acquired tuberculosis infection during long‐term anti‐TNF treatment. Abstract : What's already known about this topic? Screening for latent tuberculosis infection (LTBI) is mandatory in patients with psoriasis prior to starting on tumour necrosis factor (TNF) blockers. What does this study add? This paper evaluated the longitudinal changes of IFN‐γ response to Mycobacterium tuberculosis ‐specific antigens by serial QuantiFERON‐TB Gold In‐Tube testing in patients with psoriasis during in vivo and in vitro treatment with biological anti‐TNF therapy.